Using Flashcard Media to Increase Students’ Vocabulary Mastery - Fina Fatika Nurmala Sari; Rahmadi Nirwanto; Zaitun Qamariah (Universitas Maritim AMNI Semarang, 2023)
English language learning in elementary schools based on the 2013 curriculum is included in local content, where English language learning becomes learning that is not mandatory in elementary schools. However, some elementary schools require their students to learn English, but the schools educator shortages. At the elementary school SDN Bereng Kajang - 1, researcher found that the school has a local content teacher, but the teacher have no basic in english learning. The researcher's goal is to improve English learning through vocabulary material with flashcard media. This research uses the CAR (Classroom Action Research) method in which this research collaborates with the teacher in observing the student learning process while in the classroom. This research was conducted in 2 cycles; the sample of this study was grade 4 students and total of the students are 12. In this study, researcher are more concerned with the process of each cycle stage in order to get satisfactory results.